Effect of dietary celery (Apium graveolens) on the growth performance, immune responses, and bacterial resistance against Vibrio anguillarum of European seabass (Dicentrarchus labrax) - Güroy, Derya; Güroy, Betül; Bilen, Soner; Kenanoğlu, Osman Nezih; Şahin, İzzet; Terzi, Ertuğrul; Karadal, Onur; Mantoğlu, Serhan (Springer Science and Business Media LLC, 2022)
In this study, we evaluated to reveal the effects of aqueous methanolic extract of celery (Apium graveolens) on the growth performance, immune responses, and resistance against Vibrio anguillarum in European seabass (Dicentrarchus labrax). For this purpose, twenty fish (initial mean weight of 4.80 ± 0.06 g) were placed into twelve tanks (400 L) in triplicate and fish were fed with control (C) and three different levels (0.01, 0.05, and 0.1 g/kg) of A. graveolens (AG) extract-containing diets (AG0.01, AG0.05, and AG0.1) for 30 days. Blood and tissue (kidney, spleen, and intestine) samples were taken from the fish every 10 days during the study to determine the immune responses of the fish. Respiratory burst activity (RBA) was significantly decreased in the AG0.1 group compared to all other groups on the 10th day of the study (P < 0.05). Significance was noticed in the RBA of fish in all AG groups compared to the C group (P < 0.05) on the 30th day of the experiment Lysozyme activity (LYS) was raised on the 10th day of the study in all celery groups compared to the C group (P < 0.05). No differences in the myeloperoxidase activity (MPO) were observed among the experimental groups (P > 0.05). The final mean weight (FMW) was not affected in any experimental groups (P > 0.05). However, in the AG0.05 group, the specific growth rate (SGR) increased, and the feed conversion ratio (FCR) decreased compared to other groups (P < 0.05). IL-1β in the kidney was highly elevated in the AG0.01 group on the 20th day of the study (P < 0.05). Similar results were observed on IL-6, IL-8, and TNF-α expression in the kidney (P < 0.05). Anti-inflammatory responses (IL-10 and TGF-β) also increased in all experimental groups and tissues compared to the C group (P < 0.05). COX-2 was upregulated on the 20th day of the study in all tissues (P < 0.05). At the end of the feeding trial, the survival rate of the AG0.1 group in fish infected with Vibrio anguillarum infection was higher than the C group. Dietary celery extract did not affect growth performance directly but increased innate immune responses and a high survival rate. Overall, compared to the control group, the growth, immunity, and resistance of European seabass fed with a diet containing 0.05 g/kg celery aqueous methanolic extract has been improved, and this could be used as an immunostimulant feed additive.
Keywords: Animal Feed; Immunity, Innate; Diet; Fish Diseases; Vibrio Infections; Dietary Supplements; Animals; Bass; Disease Resistance; Vibrio; Apium; 3. Good health; 14. Life underwater